5 3 the region is shown in figure 955 our rst step is

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: ries of the region and the intervals of θ values over which these boundaries are traced out. Since the polar coordinates of a point are not unique, extra care is needed to determine these intervals of θ values. Example 2 SOLUTION r=1 r = 2 cos θ O polar axis Find the area of the region that consists of all points that lie within the circle r = 2 cos θ but outside the circle r = 1. θ= 5π 3 The region is shown in Figure 9.5.5. Our first step is to find values of θ for the two points where the circles intersect: 2 cos θ = 1, cos θ = 1 , 2 θ = 1π, 5π. 3 3 Figure 9.5.5 550 CHAPTER 9 THE CONIC SECTIONS; POLAR COORDINATES; PARAMETRIC EQUATIONS Since the region is symmetric about the polar axis, the area below the polar axis equals the area above the polar axis. Thus A=2 0 π /3 1 ([2 cos θ ]2 2 − [1]2 ) d θ . 1 2 If you carry out the integration, you will see that A = 1 π + 3 θ= π r = 1 – 2 cosθ 1 3 √ 3 ∼ 1. 91. = Example 3 limaçon Find the area A of the region between the inner and outer loops of the r = 1 − 2 cos θ . (Figure 9.5.6) SOLUTION You can verify that r = 0 at θ = π/3 and at θ = 5π/3. The outer loop is formed as θ increases from π/3 to 5π/3. Thus θ= π 5 3 area within outer loop = A1 = 5π/3 π/3 1 [1 2 − 2 cos θ ]2 d θ . Figure 9.5.6 The lower half of the inner loop is formed as θ increases from 0 to π/3, and the upper half as θ increases from 5π/3 to 2π (verify this). Therefore area within inner loop = A2 = 0 π /3 1 [1 2 − 2 cos θ ]2 d θ + 2π 5π/3 1 [1 2 − 2 cos θ ]2 d θ . Now 1 [1 2 − 2 cos θ ]2 d θ = = = 1 2 1 2 1 2 [1 − 4 cos θ + 4 cos2 θ ] d θ [1 − 4 cos θ + 2(1 + cos 2θ )] d θ [3 − 4 cos θ + 2 cos 2θ ] d θ = 1 [3θ − 4 sin θ + sin 2θ ] + C . 2 5π/3 π/3 Therefore A1 = 1 2 3θ − 4 sin θ + sin 2θ = 2π + 3 2 √ 3 and A2 = = 1 2 3θ − 4 sin θ + sin 2θ − 3 4 π /3 0 + 1 2 3θ − 4 sin θ + sin 2θ 2π 5π/3 1 π 2 √ 3+ 1 π 2 √ √ − 3 = π − 3 3. 2 3 4 Thus, A = A 1 − A 2 = 2π + 3 2 √ 3 − (π − 3 2 √ √ 3...
View Full Document

This note was uploaded on 10/12/2010 for the course MATH 12345 taught by Professor Smith during the Spring '10 term at University of Houston - Downtown.

Ask a homework question - tutors are online